2014
DOI: 10.1007/s12350-013-9846-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bone marrow mononuclear stem cell therapy on left ventricular function and myocardial perfusion

Abstract: BMC transfer appears to have a positive impact on LV recovery in patients with acute coronary syndrome and those with stable coronary disease with or without heart failure. Most studies were small and a minority used a core laboratory for image analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…Three reviews also included participants with AMI or acute coronary syndrome (ACS). 11,13, 14 The number of trials included in the systematic reviews ranged from 5 to 50. All systematic reviews included RCTs, and 3 11,14,15 also included RCTs and cohort studies.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three reviews also included participants with AMI or acute coronary syndrome (ACS). 11,13, 14 The number of trials included in the systematic reviews ranged from 5 to 50. All systematic reviews included RCTs, and 3 11,14,15 also included RCTs and cohort studies.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…13 Three systematic reviews included trials for both CIHD and AMI or ACS and pooled data from these studies for their primary meta-analysis. 11,13, 14 In subsequent subgroup analysis, 2 reviews suggested that cell therapy significantly improved LVEF in AMI patients but not in CIHD patients. 13, 14 This may be related to the number of included trials for each clinical setting; there were only 4 CIHD studies compared with 14 for AMI in one of the reviews.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells can be introduced into tissues or organs to replace diseased or damaged cells with minimal risk of rejection and side effects, and can therefore be applied for disorders of the bone/cartilage, lung, liver and diabetic diseases [1][2][3]. A large number of stem cells should be prepared to achieve satisfactory therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Cellbased therapy is a novel and potential therapeutic approach, which can replace diseased or damaged cells with minimal side effects by introducing stem cells to these tissues or organs [1][2][3][4] . Currently, BMSCs have represented the golden type of stem cell for cell-based therapies.…”
Section: Introductionmentioning
confidence: 99%